Nutrient intake, introduction of baby cereals and other complementary foods in the diets of infants and toddlers from birth to 23 months of age - Theresa A Nicklas; Carol E O'Neil; Victor L Fulgoni III (AIMS Press, 2020)
Introduction: Understanding which foods are introduced in the diet and when provides valuable information on complementary feeding. Fortified baby rice cereal is the most common first solid food given to infants, often followed by other baby cereals. The objective of this study was to examine food patterns among infants and toddlers consuming rice or non-rice baby cereals versus non-consumers. Methods: NHANES 2001-2014 data were used to assess dietary intake, nutrient adequacy, and food specific patterns of infants and toddlers. Groups were: baby cereal non-consumers (n = 3,910), non-rice baby cereal consumers (n = 711), and rice baby cereal consumers (n = 966). Those consuming both non-rice cereal and rice cereal were included in the rice cereal group (n = 9, 48, 61, and 10 for those 0-3, 4-6, 7-11, and 12-23 mos, respectively). Least-square means ± SEs were determined for nutrient intake and food group consumption by using covariate controlled regression analyses (p < 0.01). Results: Baby cereal consumer groups, compared to non-consumers, had higher intakes of carbohydrates, iron, calcium, magnesium, zinc, and vitamin E, with lower percentage having intakes below the Estimated Average Requirement for iron, calcium, and vitamin E. Infants 0-3 mos and 4-6 mos in both baby cereal consumption groups consumed other solid foods, including baby foods and beverages, sweetened beverages, coffee and tea, 100% juice, vegetables (excluding potatoes), fruit, sugars, milk and yogurt, and mixed dishes. The baby cereal consumers and non-consumers groups had intakes aligned with the "American diet". Baby cereal non-consumers had a significantly higher percentage of exclusively breast fed at ages 0-3 mos and a lower percentage formula fed. Conclusion: This study provides detailed information on the introduction of baby cereals which was associated with better nutrient intakes and other complementary foods and intakes of nutrients that require special attention during early life. Further, cow's milk products and solid foods were introduced prior to the American Academy of Pediatrics' age recommendations.